Computational tool to support design of DAC Converter model AD7528 with the object code in XML - Almeida, Tiago da Silva [UNESP]; Silva, Alexandre César Rodrigues da [UNESP]; Sampaio, Daniel Julien Barros da Silva [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Based on literature review, electronic systems design employ largely top-down methodology. The top-down methodology is vital for success in the synthesis and implementation of electronic systems. In this context, this paper presents a new computational tool, named BD2XML, to support electronic systems design. From a block diagram system of mixed-signal is generated object code in XML markup language. XML language is interesting because it has great flexibility and readability. The BD2XML was developed with object-oriented paradigm. It was used the AD7528 converter modeled in MATLAB / Simulink as a case study. The MATLAB / Simulink was chosen as a target due to its wide dissemination in academia and industry. From this case study it is possible to demonstrate the functionality of the BD2XML and make it a reflection on the design challenges. Therefore, an automatic tool for electronic systems design reduces the time and costs of the design.
Keywords: Computational methods; Converters; Objectoriented programming; Synthesis; Automatic tools; Computational tools; Converter model; Design challenges; Electronic systems; Literature reviews; MATLAB/ SIMULINK; Object-oriented paradigm; Automobile electronic equipment; Design; Digital integrated circuits; Electronics engineering; Hypertext systems; Robotics; Synthesis (chemical); Torque converters; XML; Systems analysis